2008
DOI: 10.1242/dev.028118
|View full text |Cite
|
Sign up to set email alerts
|

PTEN deficiency causes dyschondroplasia in mice by enhanced hypoxia-inducible factor 1α signaling and endoplasmic reticulum stress

Abstract: Chondrocytes within the growth plates acclimatize themselves to a variety of stresses that might otherwise disturb cell fate. The tumor suppressor PTEN (phosphatase and tensin homolog deleted from chromosome 10) has been implicated in the maintenance of cell homeostasis. However, the functions of PTEN in regulating chondrocytic adaptation to stresses remain largely unknown. In this study, we have created chondrocyte-specific Pten knockout mice (Pten co/co ;Col2a1-Cre) using the Cre-loxP system. Following AKT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 60 publications
5
42
0
1
Order By: Relevance
“…Several recent studies (Ford-Hutchinson et al, 2007;Hsieh et al, 2009) reported the use of collagen2a1 cre to delete Pten in the cartilage of developing mice and saw defects in growth plate organization along with an increase in chondrocyte differentiation and increased bone formation resulting in skeletal overgrowth. Similar experiments carried out by Yang et al (Yang et al, 2008) showed that the growth plate defects in collagen2a1 cre Pten cko mice resulted from increased endoplasmic reticulum stress in Pten-null resting chondrocytes. Other investigators (Liu et al, 2007) used an osteocalcin cre to delete Pten in mature osteoblasts.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Several recent studies (Ford-Hutchinson et al, 2007;Hsieh et al, 2009) reported the use of collagen2a1 cre to delete Pten in the cartilage of developing mice and saw defects in growth plate organization along with an increase in chondrocyte differentiation and increased bone formation resulting in skeletal overgrowth. Similar experiments carried out by Yang et al (Yang et al, 2008) showed that the growth plate defects in collagen2a1 cre Pten cko mice resulted from increased endoplasmic reticulum stress in Pten-null resting chondrocytes. Other investigators (Liu et al, 2007) used an osteocalcin cre to delete Pten in mature osteoblasts.…”
Section: Introductionsupporting
confidence: 69%
“…Recent data demonstrate that PTEN is essential for normal growth and development of skeletal cells. Conditional deletion of Pten in chondrocytes using collagen2a1 cre deleter mice leads to activation of stress response pathways and disruption of chondrocyte differentiation with development of a chondrodysplasia along with increased lipoma formation (Ford-Hutchinson et al, 2007;Yang et al, 2008;Hsieh et al, 2009). Pten deletion in end-stage, mature osteoblasts using osteocalcin cre leads to an increase in bone mass with a parallel increase in cell proliferation (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the deletion of Pten results in the accumulation of PtdIns(3,4,5)P 3 , leading to forced activation of Akt. Col2a1-Cre; Pten flox/flox mice show increased phosphorylation of Akt (Ford-Hutchinson et al, 2007;Yang et al, 2008). At 14.5 dpc, Alcian Blue staining of the skeleton showed that the degree of deformity of humeral cartilage in ; Pten +/+ proliferative chondrocytes.…”
Section: Akt Phosphorylation Is Involved In the Chondrocyte Apoptosismentioning
confidence: 98%
“…To explore the role of Zbtb20 in skeletal development in vivo, we deleted the gene specifically in the cartilaginous template of endochondral bones by mating mice with a floxed Zbtb20 allele (Xie et al, 2008) with Col2-Cre transgenic mice, a line that was reported to mediate loxP recombination specifically in cartilaginous structures at E13.5 (Yang et al, 2008;Zhang et al, 2005), when Zbtb20 protein expression is not detectable in chondrocytes. Immunohistochemical analysis showed that Zbtb20 protein is undetectable in chondrocytes of Zbtb20 chondrocyte-specific knockout embryos and postnatal mice (Zbtb20 flox/flox ;Col2-Cre, hereafter referred to as Col-ZB20KO) (Fig.…”
Section: Expression Of Zbtb20 In the Developing Mouse Skeletonmentioning
confidence: 99%